Gum chewing combined with oral intake of a semi‐liquid diet in the postoperative care of patients after gynaecologic laparoscopic surgery. Issue 19 (25th April 2017) - Pan, Yuping; Chen, Li; Zhong, Xiaorong; Feng, Suwen
Abstract : Aim and objectives: To evaluate the effects of gum chewing combined with a semi‐liquid diet on patients after gynaecologic laparoscopic surgery. Background: Previous studies suggested that chewing gum before traditional postoperative care promotes the postoperative recovery of bowel motility and function after open and laparoscopic surgery. However, gum chewing combined with a semi‐liquid diet has not been reported in postoperative care of patients following gynaecologic laparoscopic surgery. Design: A prospective randomised study. Methods: Total 234 patients were randomly assigned after elective gynaecologic laparoscopic surgery to a gum chewing and semi‐liquid diet group, a semi‐liquid only diet group or a liquid diet group. The gum chewing and semi‐liquid diet group chewed sugar‐free gum with an oral intake of a semi‐liquid diet six hours postoperatively. The semi‐liquid only diet and liquid diet groups received a semi‐liquid diet or a liquid diet, respectively. The time to first bowel sounds, time to first regular postoperative bowel sounds, time to first passage of flatus, time to first defecation, serum gastrin and incidences of hunger, nausea, vomiting and abdominal distension were recorded. Hunger and gastrointestinal sensations were assessed using a four‐point scale. Serum gastrin was assayed pre‐ and postoperatively using a gastrin radioimmunoassay kit. Results: The gum chewing and semi‐liquid diet group had first bowel sounds, first regular bowel sounds, first passage of flatus and first defecation earlier than the semi‐liquid only and liquid groups. Increased serum gastrin was observed in the gum chewing and semi‐liquid diet group. Incidences of nausea, vomiting and abdominal distention were not significantly different between these groups. Conclusion: Chewing gum combined with an oral intake of a semi‐liquid diet is safe and accelerates the postoperative recovery of bowel function. It might be recommended as a better postoperative care regimen for patients after gynaecologic laparoscopic surgery. Relevance to clinical practice: This study developed a new postoperative diet regimen to improve the postoperative care of patients undergoing laparoscopic gynecologic surgery.